(untitled) (Universal International Scientific Journal, 2026)
This article systematically analyzes the pedagogical, methodological, psychological and linguodidactic aspects of the process of independent learning of the Chinese language based on mobile applications. The main goal of the study is to identify the mechanisms for the formation of students’ self-development, independent learning and reflective thinking competencies in a digital learning environment. The article scientifically examines the didactic capabilities of mobile applications, their level of interactivity, their role in providing person-centered education, and their features of supporting individual learning rates. In the research process, experimental and theoretical methods were used to statistically analyze the impact of mobile applications on the effectiveness of learning the Chinese language. The results obtained confirm that the independent learning process organized using mobile platforms serves to increase student motivation, develop linguistic competencies, and strengthen communicative skills.